Safety and Efficacy of the HIV-1 Attachment Inhibitor Prodrug Fostemsavir in Antiretroviral-Experienced Subjects: Week 48 Analysis of AI438011, a Phase IIb, Randomized Controlled Trial. Issue 3 (April 2017) - ,; Thompson, Melanie; Lalezari, Jacob P; Kaplan, Richard; Pinedo, Yvett; Pena, Otto A Sussmann; Cahn, Pedro; Stock, David A; Joshi, Samit R; Hanna, George J; Lataillade, Max
Background: Fostemsavir is a prodrug of temsavir, an attachment inhibitor that binds directly to HIV-1 gp120, blocking initial viral attachment and entry into host CD4 + T-cells. Efficacy, safety and dose-response data of fostemsavir in treatment-experienced, HIV-1-infected subjects, through week 48, are reported. Methods: AI438011 is an ongoing Phase IIb, randomized, active-controlled trial (NCT01384734). Subjects were randomized 1:1:1:1:1 into five arms: fostemsavir (400 mg twice daily, 800 mg twice daily, 600 mg once daily or 1, 200 mg once daily) and a reference arm (ritonavir-boosted atazanavir [ATV/r] 300/100 mg once daily), each with a backbone of raltegravir 400 mg twice daily plus tenofovir disoproxil fumarate 300 mg once daily. Results: In total, 251 subjects were treated. Through week 48, the proportion of fostemsavir subjects with HIV-1 RNA <50 copies/ml was 61–82% and 77–95% (modified intent-to-treat [mITT] and observed analysis, respectively); 71% and 88% for ATV/r subjects (mITT and observed). Observed virological response rates were 74-100% versus 96% (fostemsavir versus ATV/r) in subjects with baseline viral load <100, 000 copies/ml and 60-91% versus 71% when baseline viral load was ≥100, 000 copies/ml. Across fostemsavir arms, median CD4 + T-cell count increases from baseline were 145-186 cells/μl and 142 cells/μl for the ATV/r arm. Fostemsavir doses were generally well tolerated and no fostemsavir-related adverse events led to discontinuation. Conclusions: Through week 48, fostemsavir continued to be well tolerated and showed similar efficacy to ATV/r. These results support the ongoing Phase III trial in heavily treatment-experienced adults with limited therapeutic options (≤2 classes of active antiretrovirals remaining). ClinicalTrials.gov identifer: NCT01384734.